Radial artery coronary bypass grafting: Surgical outcomes of an unexplored innovation in a developing country - Russell Seth Martins; Laiba Masood; Mabrooka Kazi; Mishal Gillani; Ayesha Sadiq; Hina Inam; Saulat Hasnain Fatimi (Journal of the Pakistan Medical Association, 2022)
Objective: To explore postoperative outcomes, particularly prolonged length of hospital stay, in radial artery coronary artery bypass graft patients in a tertiary-care setting. Methods: The pilot prospective cohort study was conducted at the Aga Khan University Hospital, Karachi, from September 2019 to September 2020, and comprised adult patients of either gender due to undergo coronary artery bypass grafting for coronary artery disease involving two or more vessels. The subjects approached for the use of their radial artery as a conduit. Prolonged length of hospital stay was defined as postoperative stay >9 days. Multivariable logistic regression was used to identify independent predictors of the length of hospital stay. Data was analysed using SPSS 21. Results: Of the 97 patients, 84(86.6%) were males. The overall mean age of the sample was 58.33±8.34 years. Mean length of hospital stay was 8.10±2.37 days, and 23(23.7%) patients had prolonged stay. Higher age was a significant predictor of prolonged hospital stay (p<0.05). Besides, 23(23.7%) patients developed acute kidney injury. There was no incidence of wound, infection or deep venous thrombosis, while 1(1.03%) patient had to be reopened due to excessive postoperative bleeding, and it represented the lone mortality. Conclusion: Patient age was found to be a significant predictor of prolonged hospital stay in patients undergoing radial artery coronary artery bypass graft, while almost a quarter of the sample was affected by acute kidney injury. Keywords: Coronary artery bypass graft, Radial artery, Prolonged length of stay, Acute kidney injury, Ejection fraction. Continuous...